Nitric oxide synthase 2 genetic variation rs2297514 associates with a decreased susceptibility to extremity post-traumatic osteomyelitis in a Chinese Han population - Song, Chen-sheng; Zhang, Ping; Lin, Qing-rong; Hu, Ying-yu; Pan, Chun-qiu; Jiang, Nan; Hu, Yan-jun (Frontiers in Cellular and Infection Microbiology, 2023)
Previous studies have indicated that nitric oxide synthase 2 (NOS2) genetic variations are involved in delayed fracture healing and fracture non-union. Whether these genetic variants associate with the development of osteomyelitis (OM) remains unclear. Here, we analyzed the potential relationships between NOS2 genetic variations and the risk of developing post-traumatic OM (PTOM) in a Chinese Han population. Altogether 704 participants, including 336 PTOM patients and 368 healthy controls, were genotyped of rs2297514 and rs2248814 of the NOS2 gene using the SNaPshot genotyping method. Outcomes showed that the frequency of allele C in the patient group was significantly lower than that in the control group (48.7% vs. 54.5%, P = 0.029, OR = 0.792, 95% CI 0.642 – 0.976). In addition, significant associations were found between rs2297514 and susceptibility to PTOM by the recessive model (P = 0.007, OR = 0.633, 95% CI 0.453 – 0.884), and the homozygous model (P = 0.039, OR = 0.648, 95% CI 0.429 – 0.979). Moreover, patients with the CC genotype of rs2297514 had lower inflammatory biomarkers levels than the TT genotype, especially for the C-reactive protein (CRP) level (median: 4.1 mg/L vs. 8.9 mg/L, P = 0.027). However, no significant relationship was noted between rs2248814 and the risk of developing PTOM. In this Chinese cohort, rs2297514 is correlated with a decreased risk of PTOM development, with genotype CC as a protective factor.